The debt with Palma - Díaz Ortiz, Pedro (2019)
Since the publication of the first edition of Peruvian Traditions by Ricardo Palma in 1872 until our days, Latin American and Peruvian writers have recognized the Tradition as a literary gender created by Ricardo Palma. However, the Royal Spanish Academy has not yet accepted the definition of the word as a literary gender. In this article we present an historic review of this situation.